A REVIEW OF KOMBUCHA ANTIOXIDANT EFFECTS ON ATHEROSCLEROSIS IN PRECLINICAL STUDIES - Elizabeth; Sharone Amabel; Ardo Sanjaya; Julia Windi Gunadi; Diana Krisanti Jasaputra (Faculty of Medicine Universitas Kristen Duta Wacana, 2023)
Background Atherosclerosis is the leading cause of death among cardiovascular diseases in Indonesia, in which death is possible if uncontrolled. The prevalence of the disease may be prevented by consuming foods or drinks containing high levels of antioxidant such as kombucha. Exploration of kombucha properties as an antioxidant that will improve atherosclerosis could be obtained from preclinical studies. Objective To discuss the antioxidant effect of kombucha on atherosclerosis in preclinical studies. Method This study is a narrative review with literatures from 2013 to 2022. Result Kombucha is an antioxidant-rich beverage made from enzymes generated by the SCOBY bacteria, which are fermented in sweet tea for 7-14 days to achieve optimal quantities of polyphenols. In addition to the antioxidants in the blood, the effect will lower the levels of LDL, VLDL, triglycerides, and total cholesterol in the blood. Moreover, it can increase HDL in blood and inhibit lesion forming in the aorta. Conclusion Polyphenol in kombucha tea has an antiatherogenic effect that may prevent atherosclerosis in preclinical studies. Keywords: antioxidant, atherosclerosis, kombucha, polyphenol